CORRELATION BETWEEN PHYSICAL AND MECHANICAL PROPERTIES OF THE WOOD - Petkov, Todor; Panayotov, Panayot (Innovation in Woodworking Industry and Engineering design, 2016)
The results of testing for the presence of correlation and how strong it is between some physical – mechanical properties - bending strength, modulus of elasticity in bending and density are established. This analysis compared the coefficients of correlation between one or more pairs of variables in order to determine statistical correlations between them. The results reflect the behavior of the test specimens made from the wood of various tree species common in Bulgaria – white pine, spruce, black pine, beech and oak.